2010
DOI: 10.1158/1055-9965.epi-10-0264
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25(OH) Vitamin D and Risk of Breast Cancer: A Nested Case-Control Study from the French E3N Cohort

Abstract: Background: High 25-hydroxyvitamin D [25(OH)D] serum concentrations have been found to be associated with reduced breast cancer risk. However, few studies have further investigated this relationship according to menopausal status, nor have they taken into account factors known to influence vitamin D status, such as dietary and serum calcium, parathyroid hormone, and estradiol serum levels.Methods: We designed a nested case-control study within the French E3N cohort. Cases were women diagnosed with incident bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
99
5
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 49 publications
15
99
5
3
Order By: Relevance
“…29 The results of these studies contributed to the result of the most recent meta-analysis 16 that revealed an inverse overall risk estimate from six prospective studies. 11,19,23,[29][30][31] However, the clear null results of our study and two other recent studies 20,21 suggest that the prospective overall relationship of 25(OH)D levels and breast cancer risk is weak in magnitude, if present at all.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…29 The results of these studies contributed to the result of the most recent meta-analysis 16 that revealed an inverse overall risk estimate from six prospective studies. 11,19,23,[29][30][31] However, the clear null results of our study and two other recent studies 20,21 suggest that the prospective overall relationship of 25(OH)D levels and breast cancer risk is weak in magnitude, if present at all.…”
Section: Discussioncontrasting
confidence: 66%
“…These cases were also part of a parallel initiative based on a total of 636 incident cases from the E3N study that independently started at the same time as our study. 19 An incidence density protocol was applied for matching. Accordingly, each control could be chosen more than once and also become a case at a later time point.…”
Section: Cases and Controlsmentioning
confidence: 99%
See 2 more Smart Citations
“…This reduced BC risk was even more pronounced in premenopausal women. Another European study also found an inverse association between BC risk and 25(OH)D 3 serum levels after a follow-up of w10 years, which was also more pronounced in younger women (Engel et al 2010). On the other hand, a Swedish study found a weak association after a follow-up of 10-15 years (Almquist et al 2010).…”
Section: Human Studies Vdr Cyp27b1 and Cyp24a1 Expressions In Cancermentioning
confidence: 94%